ICT in schools and intercultural education in Bolivia. Challenges of digital inclusion - Costas, Vladimir; Blanco, Leticia (Memorias y Boletines de la Universidad del Azuay, 2020)
This document attempts to get the challenges and opportunities in the use of ICT and inclusion in the educational process in Bolivia. The analysis is the application of a structured questionnaire to interview under qualitative research. The interview collects perceptions and perspectives from two teachers, who work with ICT and inclusion in the education field. The interviewees have long experience introducing ICT in education. The results can aim in the reflection and contrast the evolution of ICT in education towards improvements by interested stakeholders. Keywords: digital inclusion, digital literacy, special education, postgraduate education, information society.